CARACTERISATION DE LA DEFORMATION DANS LE SYNCLINORIUM DE L’ITOMBWE (KIBARIEN SUPERIEUR) A KAZIBA. SUD-KIVU , R.D.CONGO PAR - Espoir Mugisho Birhenjira; Patient Migombano Useni; Kapajika Badibanga; Mukungilwa Myango (European Scientific Journal, ESJ, 2014)
Kaziba structural survey shows that the deformations of the Itombwe synclinorium rocks and some conglomeratic intrusions integrates in a domain of the big distortions that is in relation to the evolution of the Rift Est-Africain. Microtectonic analysis puts in evidence two major phases of distortion: the first D1 that corresponds, has the regional scale, has the second phase of kibarienne deformation (paroxysmal phase), and the second, D2. - a first phase (D1) is translated by the major fold oriented N160°E as well as all structures being him subparallel (N-S to NW-SE) as the veins that have a preferential direction of N165°E with a dip of 85°ENE. - a posterior phase (D2) that would contain all secant structures to the first phase. The major fold, constructed from S0, is oriented N160°E with and dips 88°ENE and his axial plan is oriented N159°E with a dip of 13°SSE. Among the micro folds observed on land, one only (micro fold) oriented N178°E is more or less subparallel to the major fold. The other micro folds oriented N110°E and N37°E would have a sedimentary origin (slump), it is has say prelithification or syn-sedimentation because they possess some axes greatly dispersed. The dynamic or tectonic interpretation of the fracturation on canvas of Wullf permits to determine the orientation of the main vectors stress having generated the diaclasis and the veins. For the set of the diaclasis of the studied sector, two poles (P1 and P2) oriented respectively N152°E/28°NNW and N146°E/20°SE permitted to determine the slip plan (N150°E/83°E) as well as the maximal stress σ1 (N103°E/82°ESE) and the stress σ2 (N60°E/09°WSW) and σ3 (N149°E/04°NNW). Shear maximal stress τmax oriented N156°E/48°NNW. The internal friction angle φ is null (it means that there is instability).